PENANGANAN PASCA PANEN DENGAN METODE PENYIMPANAN UNTUK MENGHASILKAN BENIH PADI GOGO (Oryza sativa L.) LOKAL YANG BERKUALITAS - Mustakim; Abdul Syakur; Moh. Adnan Khaliq; Yusran (Jurnal Agrotech, 2020)
Post harvest handling is very important to produce quality and high quality seeds. The purpose of this study was to obtain the best post-harvest handling with different storage methods to produce quality and quality seeds with the best germination. This research was conducted in Tamarenja Village (Kalama Valley), Sindue Tobata District, Donggala Regency and seed testing was carried out at the Seed Science and Technology Laboratory, Faculty of Agriculture, Tadulako University. This research was conducted from October 2019 to February 2020. This research was arranged using a two-factor factorial randomized block design (RBD), the first factor consisting of two storage areas, namely: P1 = indoors, P2 = outdoors, while the second factor consists of three storage times, namely: W1 = one month and W2 = two months, and W3 = three months, which was repeated six times so that there were 36 experimental units where each experimental unit consisted of 50 seeds with a total of 1,800 seeds used. Data analysis used Fisher's test and continued with the BNJ test at 1% level. The results showed that the yields stored by hanging outdoors for 3 three months resulted in germination (71.00%), germination time (2.23 days), percentage of moldy seeds (9.33%), and percentage of moldy sprouts (9.33%).